2022
DOI: 10.1021/jacs.1c13626
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Interaction Affinity Gradient Drives [4Fe–4S] Cluster Insertion in Human Lipoyl Synthase

Abstract: Human lipoyl synthase (LIAS) is an enzyme containing two [4Fe−4S] clusters (named FeS RS and FeS aux ) involved in the biosynthesis of the lipoyl cofactor. The mechanism by which a [4Fe−4S] cluster is inserted into LIAS has thus far remained elusive. Here we show that NFU1 and ISCA1 of the mitochondrial iron−sulfur cluster assembly machinery, via forming a heterodimeric complex, are the key factors for the insertion of a [4Fe−4S] cluster into the FeS RS site of LIAS. In this process, the crucial actor is the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…While the molecular mechanism involving IND1 in the insertion of the [4Fe-4S] 2+ cluster into complex I is not yet characterized, the insertion of the [4Fe-4S] 2+ cluster into LIAS has been deeply investigated. Sequential protein–protein interactions involving ISCA1 and NFU1 have been shown to be responsible for the insertion of the [4Fe-4S] cluster into LIAS [ 32 , 33 ]. LIAS is a member of the radical S-adenosylmethionine (SAM) superfamily [ 34 , 35 ].…”
Section: [4fe-4s] Cluster Assembly In Mitochondriamentioning
confidence: 99%
See 4 more Smart Citations
“…While the molecular mechanism involving IND1 in the insertion of the [4Fe-4S] 2+ cluster into complex I is not yet characterized, the insertion of the [4Fe-4S] 2+ cluster into LIAS has been deeply investigated. Sequential protein–protein interactions involving ISCA1 and NFU1 have been shown to be responsible for the insertion of the [4Fe-4S] cluster into LIAS [ 32 , 33 ]. LIAS is a member of the radical S-adenosylmethionine (SAM) superfamily [ 34 , 35 ].…”
Section: [4fe-4s] Cluster Assembly In Mitochondriamentioning
confidence: 99%
“…It catalyzes the final step of the biosynthesis of lipoyl cofactor [ 36 , 37 , 38 ] and binds two [4Fe-4S] clusters [ 39 , 40 ]: a [4Fe-4S] cluster (FeS RS ), typical of all radical SAM enzymes, and a [4Fe-4S] cluster (FeS aux ) that provides two sulfur atoms to the lipoyl cofactor [ 41 , 42 ]. It has been shown that the C-domain of NFU1 drives first [4Fe-4S] 2+ cluster delivery from the ISCA1-ISCA2 complex, where the [4Fe-4S] 2+ cluster is assembled, to a [4Fe-4S] 2+ ISCA1-NFU1 intermediate complex, which then specifically directs the cluster into the FeS RS site of LIAS [ 32 , 33 ]. According to this molecular function, NFU1 has been shown to form two hetero-complexes with ISCA1 and LIAS [ 32 , 33 ].…”
Section: [4fe-4s] Cluster Assembly In Mitochondriamentioning
confidence: 99%
See 3 more Smart Citations